Proyecto de inversión y desarrollo para un tecnicentro automotriz multimarcas en la ciudad de Guayaquil - Beltrán Lozano, Luis Alexander (2019)
This business plan is entitled "Investment and development project for a multi-brand automotive technicentro in Guayaquil". Within the collected research, it was possible to identify that the northern sector of Guayaquil has a considerable number of automotive units that are growing every day according to the population growth of these sectors that demand quality in the service and that provide permanent benefits, creating the need to satisfy an unsatisfied demand of the users. The focus of the research is quantitative, to obtain a real focus. The study is descriptive and explanatory, the determination of the applicability of the study is based on the theoretical scientific basis, both in technical and operational aspects, and is equally beneficial for the parties………